IDENTIFIKASI SENYAWA FLAVANOID DAUN SEMBUNG (Blumea balsamifera L.) - Ahmad Ruhardi; Muhamad Handoyo Sahumena (State University of Gorontalo, 2021)
The purpose of this study was to determine the levels of flavonoids contained in the sembung leaf methanol extract. To identify the flavonoid content, Spectrophotometry UV-Vis method. Further, the analysis of methanol extract flavonoid in sembung leaves was carried out at a wavelength of 382 nm with successive absorbance values of 0.094; 0.090; 0.084. The total content of flavonoids in the sample was calculated by calibrating the absorbance value of the example with a standard linear equation of quercetin, y = 0.060 x -0.016 with a correlation coefficient (R2) = 0.997, and; the average total flavonoid content in the methanol extract of the leaves was 0.175%.